1980
DOI: 10.1016/s0022-5347(17)55497-x
|View full text |Cite
|
Sign up to set email alerts
|

Dibromochloropropane and its Effect on Testicular Function in Man

Abstract: This study represents the largest series to date documenting the gonadotoxic effect in humans of dibromochloropropane, a widely used pesticide. Three semen analyses, serum hormonal determinations (luteinizing hormone, follicle-stimulating hormone and testosterone) as well as genital examinations were completed for 228 workers at 2 chemical production sites and consisting of a dibromochloropropane-exposed and non-exposed cohort. Parameteric and non-parametric statistical analyses of the data sets of the sperm d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

1986
1986
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(23 citation statements)
references
References 13 publications
0
21
0
1
Order By: Relevance
“…Slutsky et al in his report which represents the largest cohort of DBCP exposed workers, found that after a median exposure of three years, 64.3% of these men overall, and 90.1% of men studied from the Philippines, had oligospermia or azoospermia (1999). Whorton et al (1977), Potashnik et al (1978), Lipshultz et al (1980) and Egnatz et al (1980) had the same results of a significant association. There are five studies more involving DBCP, but related to sperm recovery after cessation of exposure and are cited in the related paragraph.…”
Section: Studies With Evidence Of An Associationmentioning
confidence: 65%
“…Slutsky et al in his report which represents the largest cohort of DBCP exposed workers, found that after a median exposure of three years, 64.3% of these men overall, and 90.1% of men studied from the Philippines, had oligospermia or azoospermia (1999). Whorton et al (1977), Potashnik et al (1978), Lipshultz et al (1980) and Egnatz et al (1980) had the same results of a significant association. There are five studies more involving DBCP, but related to sperm recovery after cessation of exposure and are cited in the related paragraph.…”
Section: Studies With Evidence Of An Associationmentioning
confidence: 65%
“…22 Slutsky et al in his report which represents the largest cohort of DBCP(Dibromochloroprppane) exposed workers, found that after a median exposure of three years, 64.3% of these men overall, and 90.1% of men studied from the Philippines, had oligospermia or azoospermia . 23 The study by Whorton et al (1977), Potashniket al (1978), Lipshultz et al (1980) and Egnatz et al (1980) had the same results of a significant association between exposure to pesticides and semen quality . 24,25,26,27 .…”
Section: Discussionmentioning
confidence: 75%
“…23 The study by Whorton et al (1977), Potashniket al (1978), Lipshultz et al (1980) and Egnatz et al (1980) had the same results of a significant association between exposure to pesticides and semen quality . 24,25,26,27 . Some of the studies are not in association with our study.…”
Section: Discussionmentioning
confidence: 75%
“…Serum levels of follicle-stimulating hormone tended to be increased in exposed workers (42,97,131,132). Elevated levels of luteinizing hormones have been found in some studies (42,170), but not in others (131,132).…”
Section: Dibromochloropropane (Dbcp)mentioning
confidence: 95%